Seasonality of hydraulic redistribution by trees to grasses and changes in their water‐source use that change tree–grass interactions. Issue 2 (20th March 2015) - Priyadarshini, K. V. R.; Prins, Herbert H. T.; de Bie, Steven; Heitkönig, Ignas M. A.; Woodborne, Stephan; Gort, Gerrit; Kirkman, Kevin; Ludwig, Fulco; Dawson, Todd E.; de Kroon, Hans
Abstract: Savanna vegetation is characterized by tree–grass co‐existence that can experience intense water limitation, yet the water relations of these savanna plants are poorly understood. We examined the water sources for trees and grasses in different seasons and investigated the importance of hydraulic redistribution in three tree species inhabiting a semi‐arid savanna in South Africa. We used natural variation in H and O stable isotope composition of source waters to identify the principal water sources for these plants. We conducted an experiment by labelling deep‐soil (2.5‐m depth) with a deuterium tracer. Seasonal differences in the stable isotope composition of water in trees and grasses indicated that there was water‐source use partitioning as well as overlap. Trees and grasses used water from the topsoil after rainfall indicating overlap of water‐source use. All tree species shifted to groundwater or subsoil water use when there was no water in the topsoil indicating partitioning of water use. Grasses always used water from the topsoil. The seasonal changes in water‐source use by trees and grasses indicated possible shifts in tree–grass interactions during different periods of the year. The tracer experiment confirmed hydraulic redistribution in all the three tree species and water transfer to grasses via the topsoil. However, this occurred only in the dry season. Our observations and experimental results indicate the potential for facilitation effects by trees to their understory grasses and show that dry season hydraulic redistribution from trees to grasses could be an important facilitative mechanism maintaining tree–grass co‐existence in savannas. Copyright © 2015 John Wiley & Sons, Ltd.